Accounting Misdeeds at General Electric - Pathak, Rajesh; Geeta; Kumar, Satish (Indian Journal of Finance, 2015)
The case discussed the accounting fraudulent activities at the U.S. - based market leader of electronics industry, General Electric (GE). SEC suspected that between 2002 and 2003, GE bent the accounting rules to either inflate earnings or hit the analysts’ consensus earnings expectations. In 2005, SEC initiated an investigation and filed a complaint alleging the conglomerate of using improper hedge accounting and revenue recognition schemes that misled the investors. In August 2009, GE settled the claim, without admitting or denying allegations, by paying the SEC a 50 million penalty in response to this civil suit filed against the company. The case encouraged debate over the intentions of GE, since in the past, similar fraud cases were reported against this electronics giant. Moreover, the ethical implications of such irregular accounting practices were also discussed as GE had hurt and cheated its investors by indulging in such unethical practices.